Lumbar spine pathologies diagnosed by conventional radiography - Chancasanampa Vega, John (2025)
The objective of this research work was to identify the most frequent lumbar spine pathologies diagnosed by conventional radiography at the Daniel Alcides Carrión Regional Clinical and Surgical Teaching Hospital (HRDCQDAC), Huancayo, Peru, during 2015. An observational, descriptive, cross-sectional, retrospective study was conducted in the Diagnostic Imaging Department of HRDCQDAC, which included all lumbar radiographs from the Radiology Service of patients from the Outpatient Clinic, from January to December 2015. 111 lumbar spine radiographs were studied, 16.2% were reported as normal and 83.7% as pathological. Within the pathological radiographs, 55.9% and 44.1% corresponded to females and males respectively. Adults over 60 years of age (50.5%) presented an x-ray with some pathological finding. Between the ages of 40 and 59, the incidence was 40.9%, followed by the 13- to 39-year-old group (8.6%). The most common pathology was spondyloarthrosis (40.5%), followed by spondylosis (19.8%), followed by fractures (6.3%), lumbosacral instability (4.5%), spondylolisthesis (3.6%), and scoliosis (3.6%). Furthermore, in cases of spondyloarthrosis, 4.5% were associated with scoliosis and 7.2% with spondylolisthesis. The most frequent pathologies were spondyloarthrosis and spondylosis, being more common after age 40 and predominantly among women.